The Relationship between Accreditation Status and Public Health Centre Patient Satisfaction in Cirebon on 2021 - Amin, Muhammad; Prasetyo, Sabarinah (International Journal of Social Service and Research, 2023)
Accreditation is a mandatory process that must be carried out by public health center in order to improve the quality of health services provided to patients with an output in the form of an accredited status level. Service quality is a measure of how well the level of service provided is in accordance with customer expectations so that it affects customer satisfaction. The study was purposed to find out the relationship between the accreditation status and the level of health centers patient satisfaction in Cirebon City. Data was collected by the 2021 Community Satisfaction Survey of health centers in Cirebon City. The type of research is quantitative research with a cross-sectional approach which was conducted in November 2021 at 2 plenary accredited health centers, 3 main accredited health centers, 11 middle accredited health centers and 6 basic accredited health centers. The study sample was taken from patients who visited the health center during the study period with a total of 8180 respondents using purposive sampling method. Statistical analysis using chi square test and simple logistic regression with 95% confidence level. The results showed that 98.8% of plenary accredited primary health centers were satisfied, 95.1% of main accredited health centers, 84.2% of middle accredited health centers and 82.0% of basic accredited health centers. Based on the results of the chi-square test, the higher the accreditation status of the health centers, the higher the percentage of patient satisfaction. The results of a simple logistic regression test with a comparison of basic accredited status show that OR = 1.170 for middle accredited status, OR = 4.278 for main accredited status and OR = 18.048 for plenary accredited status. It is necessary to improve the quality of services that focus on improving services which are still low and continue to strive to meet the service standards required for health center accreditation.